(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Anthracnose fruit rot, caused by Colletotrichum coccodes, is a major constraint to tomato (Solanum lycopersicum) production worldwide, leading to significant yield and postharvest losses. Conventional chemical control methods pose challenges such as pathogen resistance, environmental contamination, and high costs; hence, the need to explore eco-friendly alternatives. This study investigated the antagonistic potential of endophytic fungi — Trichoderma sp., Aspergillus flavus, Aspergillus niger, and Rhizopus sp., against C. coccodes disease of tomato under in vitro conditions. Endophytes were isolated from healthy tomato tissues collected from Adamawa and Gombe States, Nigeria, and identified morphologically. Dual culture assays were used to assess antagonistic interactions. Results showed that all endophytic isolates significantly inhibited the growth of C. coccodes (P < 0.05), though inhibition levels varied among species. Trichoderma sp. exhibited the highest antagonistic activity (up to 12.33 mm inhibition zone at day 7), followed by Rhizopus sp. (10.68 mm), A. niger (10.52 mm), and A. flavus (10.25 mm). Mechanisms observed included antibiosis, mycoparasitism, and competition for nutrients and space. The findings demonstrate that these endophytic fungi possess strong biocontrol potential against tomato anthracnose. Trichoderma sp., in particular, could be further developed as a biological control agent within integrated disease management programs. Future studies should focus on field validation and formulation of effective endophytic inoculants for sustainable tomato production.